Gender roles during COVID‐19 pandemic: The experiences of Turkish female academics - Parlak, Simel (Gend Work Organ, 2021)
This study aims to explore the COVID‐19 experiences of Turkish female academics in terms of gender roles by focusing on how these women have dealt with domestic and academic responsibilities. The study group consisted of 21 female academics working from home, along with their spouses. Interpretative phenomenological analysis was used to analyze the data collected through semistructured telephone interviews. The findings were clustered under five main themes: the early days of the pandemic, work life after the pandemic, domestic responsibilities after the pandemic, family relationships after the pandemic, and the perception of gender roles. The results indicate that the pandemic has deepened gender inequalities, and the academic life of female academics has changed in terms of academic productivity. Therefore, we recommend that more research examining the quarantine process and involving women in other occupations and of different socioeconomic statuses should be done to develop more effective social policies.